Anisotropic mass ejection in binary mergers - Morris, T; Podsiadlowski, P (2005)
We investigate the mass loss from a rotationally distorted envelope following the early, rapid in-spiral of a companion star inside a common envelope. For initially wide, massive binaries (M_1+M_2=20M_{\odot}, P\sim 10 yr), the primary has a convective envelope at the onset of mass transfer and is able to store much of the available orbital angular momentum in its expanded envelope. Three-dimensional smoothed particle hydrodynamics calculations show that mass loss is enhanced at mid-latitudes due to shock reflection from a torus-shaped outer envelope. Mass ejection in the equatorial plane is completely suppressed if the shock wave is too weak to penetrate the outer envelope in the equatorial direction (typically when the energy deposited in the star is less than about one-third of the binding energy of the envelope). We present a parameter study to show how the geometry of the ejecta depends on the angular momentum and the energy deposited in the envelope during a merging event. Applications to the nearly axisymmetric, but very non-spherical nebulae around SN1987A and Sheridan 25 are discussed, as well as possible links to RY Scuti and the Small Magellanic Cloud object R4.